2005
DOI: 10.3748/wjg.v11.i42.6601
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of CD44s, CD44v6, and nm23 mRNA in human cancer

Abstract: Patients with overexpression of CD44s and CD44v6 and low expression of nm23 mRNA have a higher lymph node metastatic rate and invasion. In addition, overexpression of CD44v6 is closely related to the degree of cell differentiation. Detection of the three genes is able to provide a reliable index to evaluate the invasion and metastasis of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 15 publications
4
48
2
1
Order By: Relevance
“…A significant heterogeneity was observed among these included studies in this meta-analysis, and through the subgroup analysis, we can see the heterogeneity may be produced by the cut-off scores, ethnicity, year of publication and follow-up period. We also noticed that some studies had examined CD44v6 expression in NSCLC patients using methods other than immunohistochemistry (Miyoshi et al, 1997;Lee et al, 2005;Liu et al, 2005). Using reverse transcription PCR, Lee found that CD44v6 low expression was correlated to short disease-free interval and overall survival in NSCLC (Lee et al, 2005), this result was conflict with our meta-analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…A significant heterogeneity was observed among these included studies in this meta-analysis, and through the subgroup analysis, we can see the heterogeneity may be produced by the cut-off scores, ethnicity, year of publication and follow-up period. We also noticed that some studies had examined CD44v6 expression in NSCLC patients using methods other than immunohistochemistry (Miyoshi et al, 1997;Lee et al, 2005;Liu et al, 2005). Using reverse transcription PCR, Lee found that CD44v6 low expression was correlated to short disease-free interval and overall survival in NSCLC (Lee et al, 2005), this result was conflict with our meta-analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…51,52 At variance with other reports, in the present series, no significant relationship was found with histotypes of GC.…”
Section: Cd44v6 In Gastric Cancercontrasting
confidence: 57%
“…This finding suggests that this protein plays a role in the chain of events involved in neoplastic changes. The NM23 gene codifies subunits of nucleoside diphosphate kinase protein involved in cell differentiation (7,24,28) . NM23 expression is therefore expected to be increased in processes of cell multiplication.…”
Section: Discussionmentioning
confidence: 99%